Effects of Acamprosate on Sleep During Alcohol Withdrawal: A Double-Blind Placebo-Controlled Polysomnographic Study in Alcohol-Dependent Subjects - Luc, Staner; Peter, Boeijinga; Thierry, Danel; Isabelle, Gendre; Muriel, Muzet; Frédéric, Landron; Rémy, Luthringer (Alcoholism, clinical and experimental research, 2006)
Background: Sleep disturbances are frequently encountered in alcohol‐dependent patients. Drugs improving sleep during abstinence from alcohol may play an important role in the recovery process. Methods: In the present study, the effects of acamprosate, a drug successfully used in maintaining abstinence following alcohol withdrawal, were assessed by polysomnographic recordings. A parallel double‐blind placebo‐controlled study was conducted in 24 male DSM‐IV alcohol‐dependent subjects aged 35.9±1.2 years. Treatments (2 tablets of 333 mg acamprosate vs placebo t.i.d.) were initiated 8 days before alcohol withdrawal and continued during the 15 days following alcohol withdrawal. Polysomnographic assessments were recorded during acute withdrawal (the first 2 nights following withdrawal) and during postwithdrawal abstinence (the last 2 nights of the trial). Results: Results show that, compared with placebo, acamprosate decreased wake time after sleep onset and increased stage 3 and REM sleep latency (all treatment effects with a p<0.05 significance). Withdrawal effects themselves were also demonstrated as sleep efficiency (p<0.01) and total sleep time (p<0.05) were lower in abstinence nights versus withdrawal nights, whereas no significant treatment × withdrawal effect could be evidenced. Acamprosate was well tolerated during the entire course of the study. Conclusions: The present study shows that acamprosate ameliorates both sleep continuity and sleep architecture parameters classically described as disturbed in alcohol‐dependent patients. From a clinical perspective, it suggests that an 8‐day acamprosate prewithdrawal treatment is well tolerated and can attenuate the sleep disturbances engendered by alcohol withdrawal in alcohol‐dependent subjects.